PENGELOLAAN DAN PENGEMBANGAN KARIR TENAGA PENDIDIK DALAM ORGANISASI - erwin putubasai; Asmaria Asmaria; M. Fikri Akbar (Universitas Bandar Lampung (UBL), 2020)
Careers involve identifying career-related goals and preparing plans to achieve goals in the workplace organization. Realistic career planning forces individuals to see opportunities that exist in relation to their abilities. Career planning for educational staff is a process by which educational staff can identify and take steps to achieve their career goals in the world of education. This writing uses the literature review method. Literature review is used to look for theories or concepts related to the selection and planning of change strategies. The management and career planning of the education staff is ultimately the responsibility of the education staff themselves. But educational organizations or institutions, of course, must intervene and play a role in the form of assistance to motivate educational staff to achieve their career goals. The role of organizations here can be in the form of providing career education, career information, and career guidance, and specifically providing orientation, training, creating fair promotions, and others.